AN AUTO-MANAGEMENT THESIS PROGRAM WEB-MIS SUPPORTED WORKFLOW - CHANG, TAUG; KAN-DING, PANIG; L, FEN (International Journal of Multidisciplinary Research and Studies, 2021)
An auto-management Web-MIS supported workflow for the bachelor thesis program is given during this paper. A module used for workflow dispatching is meant and realized using MySQL and J2EE per the working rule of the workflow engine. The module can automatically dispatch the workflow in line with the date of the system, login information, and user’s work status. The WebMIS changes the management from handwork to computer work, which standardizes the thesis program and keeps the information and documents clean and consistent.